Literature review on energy consumption and conservation in mobile device - Ali, Abdifatah Farah; Mohd Hatta, Najwa Hanis; Koh, Tieng Wei (Asian Research Publication Network, 2017)
Mobile devices are increasing in number today. Consequently, computational resources are growing in tandem. Energy consumption has become a major issue all over the globe. On mobile devices (smart phones),there is a huge gap between battery power capabilities as well as innovations with other technologies (for example, developing and also memory space), this is especially the case with examining the rapid development in its consumed energy-lost mobile phone in different area (such as, multimedia streaming). Most of the insufficient power supplies and also the need for minimizing energy depletion offers the commitment for professionals to create energy consumption techniques or model for cominggeneration wireless network. Based on the above, it is necessary to take the approach for energy consumption minimization and improvement of energy conservation into consideration. This could help achieve the desire of green technology for using less energy power in mobile devices. To gain this aim is it possible? Consequently, heterogeneous approach in energy consumption and conservation in mobile device which have been proposed by various researchers has been investigated in this paper. This would help to put in proper perspective the different energy consumption models directed at energy conservation.